Rose-Mamba-YOLO: an enhanced framework for efficient and accurate greenhouse rose monitoring - You, Sicheng; Li, Boheng; Chen, Yijia; Ren, Zhiyan; Liu, Yongying; Wu, Qingyang; Tao, Jianghan; Zhang, Zhijie; Zhang, Chenyu; Xue, Feng; Chen, Yulun; Zhang, Guochen; et al. (Frontiers in Plant Science, 2025)
Accurately detecting roses in UAV-captured greenhouse imagery presents significant challenges due to occlusions, scale variability, and complex environmental conditions. To address these issues, this study introduces ROSE-MAMBA-YOLO, a hybrid detection framework that combines the efficiency of YOLOv11 with Mamba-inspired state-space modeling to enhance feature extraction, multi-scale fusion, and contextual representation. The model achieves a mAP@50 of 87.5%, precision of 90.4%, and recall of 83.1%, surpassing state-of-the-art object detection models. Extensive evaluations validate its robustness against degraded input data and adaptability across diverse datasets. These results demonstrate the applicability of ROSE-MAMBA-YOLO in complex agricultural scenarios. With its lightweight design and real-time capability, the framework provides a scalable and efficient solution for UAV-based rose monitoring, and offers a practical approach for precision floriculture. It sets the stage for integrating advanced detection technologies into real-time crop monitoring systems, advancing intelligent, data-driven agriculture.